Tafsir Al-Qur’an Berbahasa Bugis (tpEeser akor mbs aogi) Karya AGH. Abd. Muin Yusuf - Muhsin Mahfudz (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2011)
This article discuss about the method of Qur’anic exegesis (Tafsir) written in local languages. For more focus on it, the article analyzes the method which is used by Anregurutta (an Islamic teacher) H. Abd. Muin Yusuf in his Tafsir, Tafsere Akorang Mabbasa Ogi (Qur’anic Commentary in Bugisnes Language), one of the famous Tafsirs which is written in local languages in South Sulawesi (Bugis-Makassar). It emerges some questions such as, do the local Tafsir has a different method from another Arabic Tafsirs? or is it just the same?. Based on those questions, the article tries to examine, by using the Exegetical Approach, the characteristics of method which is used in the Tafsere. After exploring with the content analysis, it is discovered that the writing style of the Tafsere imitated the style of al-Tafsir al-Wadhih written by Syekh Muhammad Mahmud Hijazi. Nevertheless, Anregurutta gave some modifications based on the other resources. What interesting thing in his work is the decision made by Anregurutta to choose the moderation way in quoting different argumentation of understanding the Qur’an. As a result, the Tafsere gives an impression that every disagreement should be appreciated without tendencies to the certain mazhab (theological/law school). In addition, the Anregurutta unclearly supported to one of or both al-tafsir bi al-ma’tsur (traditional commentary) and al-tafsir bi al-ra’y (rational commentery), even he smoothly compromised them in many places. However, the Tafsere is like an “untouchable treasure” because only a muslim who has master Lontara (Bugis Alphabet) can read it.